Parasites of the invasive Chinese sleeper Perccottus glenii (Actinopterygii: Odontobutidae) in the region of the first introduction of the Carpathian population - Kvach Yuriy; Kutsokon Yuliya; Janáč Michal; Dykyy Ihor; Dzyziuk Natalia; Dudliv Ivanna; Nazaruk Kateryna (Oceanological and Hydrobiological Studies)
Parasites of the invasive Chinese sleeper (Perccottus glenii) were studied in five different localities at the site of the first introduction of the Carpathian population of this fish. We recorded eight taxa of parasites in Lviv water bodies. The monogenean Gyrodactylus perccotti and the cestode Nippoteania perccotti were recorded in all five lakes studied. These parasites represent Far East species introduced together with their host. Also the copepod Neoergasilus japonicus is a Far East parasite introduced to Europe with its aquaculture vector. Differences between the surveyed bodies of water were mainly related to their local seasonal conditions and watershed characteristics. The current data confirm the presence of co-introduced populations of G. perccotti and N. perccotti, which probably affects the future invasiveness of their host. Due to low acquisition of local parasites, we cannot confirm any significant effect of invasive fish on local parasite assemblages in this region. However, the presence of the non-indigenous copepod, N. japonicus, requires additional attention in the future.